Urban flash flood and extreme rainfall events trend analysis in Bamako, Mali - FOFANA, Mohamed; ADOUNKPE, GNONLONFOUN JULIEN (My University, 2022)
One of the consequences of climate change is the increasing rainfall intensity and frequency leading to flooding Lately, some major cities in West Africa have been experiencing high frequency of flooding due to extreme rainfall This study investigated the temporal trends in flash flood and extreme rainfall events in Bamako, Mali for the period 1982–2019. Rainfall observation data from both Mali Meteorological Agency and Climate Hazards Group Infrared Precipitation, and flood ground information’ collected from the Mali Civil protection service were used for this study. Five rainfall extreme indices established by Expert Team for Climate Change Detection Monitoring and Indices (ETCCDI) were analyzed to characterize extreme rainfall intensity and frequency indices. The Gumbel extreme value distribution was used to estimate the return period of flood and extreme rainfall for the period of 5 to 100 years based on the annual maximum daily rainfall. All the five extreme rainfall indices displayed an upward trends except the consecutive wet days (CWD) that showed a decreasing trend. Both the intensity and frequency of extreme rainfall were found to have increased over the study period. The analysis of the flood reports showed an increasing trend in Bamako from 1982 to 2019. The returned period revealed that about 58% of flood events in Bamako are caused by normal rainfall, with 33.3% being caused by extreme rainfall. It was also determined that most flood events were recorded in the years that had higher number of extremely wet days The findings from this study have demonstrated that floods in Mali are prevalent and adaptation and mitigation strategies are needed.
Keywords: Extreme rainfall indices Flood Return period Rainfall event Bamako